Dukkha dan Ekologi Integral: Berpikir secara Ekologis di Sri Lanka Pasca-Perang - Ranawana, Anupama (Indonesian Journal of Theology, 2025)
Ecological thinking in contexts such as Sri Lanka, which is recovering from long-term war, must attend to multiple dimensions of the ecological crisis. At first, it is important to consider the ways in which a war that has ranged for several decades has had significant ecological impacts on land, air, and waterways. It is necessary to understand that climate events—heavy flooding and tsunamis—continued to occur throughout the thirty years of war between the Sri Lankan State and the Liberation Tigers of Tamil Eelam (LTTE). A further complexity to add here is the fact that the state mechanism has consistently grabbed land from minority communities, particularly the Tamil and Indigenous communities, during the war years. This has worked to degrade the relationship between communities and their sacred lands. This paper reflects upon these multiple impacts and argues for the importance of dukkha or suffering as a concept that must be centered in ecotheology focused on Sri Lanka. The article is written in dialogue with Sister Rasika Pieris’s work, which narrativizes suffering from the position of Buddhist and Catholic widows in Sri Lanka, to consider how we might mourn with Creation in the same way as we might with a widow. How do we think about suffering when Creation is multiply ravaged? What are the implications for ecotheology?